Cash is more than a public good - Héctor Labat; Franz Seitz; Guillaume Lepecq (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2024)
In September 2023, CashEssentials launched a research project addressing the questions 'Is cash a public good? Is it a basic right?' with the aim of clarifying the debate and advancing policies. Within this framework, Labat (2024) reviewed the literature on the topic, offering a comprehensive taxonomy to frame the discussion. A research seminar was then held in Istanbul on 6 November, bringing together a multidisciplinary panel of international specialists: * Héctor Labat, Research Fellow, CashEssentials * Tim Stuchtey Brandenburg Institute for Society and Security * Frédéric Allemand, Robert Schuman Institute, University of Luxembourg * Carin van der Cruijsen, De Nederlandsche Bank * Franz Seitz, Weiden Technical University of Applied Sciences, Weiden * Ursula Dalinghaus, Ripon College. The present document summarizes the main take-aways of the research project and the discussions at the research seminar. We would like to extend our warm gratitude to both the panelists and the participants who have made this research possible. – – Im vorliegenden Papier untersuchen wir die Frage, ob Bargeld ein öffentliches Gut ist und es ein Grundrecht auf Bargeldverwendung gibt. In einem strikten Sinne ist Bargeld kein öffentliches Gut, das in den Wirtschaftswissenschaften über Nicht-Rivalität im Konsum und Nicht-Anwendbarkeit des Ausschlussprinzips definiert wird. Allerdings trägt die Institution "Bargeld" zu einigen positiven gesellschaftlichen (mikro- und makroökonomischen) Entwicklungen bei, die öffentlichen Gutscharakter besitzen. Darunter fallen z. B. Anonymität und Schutz der Privatsphäre, Zahlungsmittelinklusion, Stabilisierungseigenschaften in Krisenphasen oder Sicherstellung des Wettbewerbs auf den Zahlungsverkehrsmärkten. Wenn das akzeptiert wird, impliziert dies eine stärkere Rolle des öffentlichen Sektors im Bargeldkreislauf. Dies sollte für eine intakte Bargeldinfrastruktur sorgen mit profitablen privaten Geschäftsmodellen. Es bedeutet jedoch nicht, dass es ein verfassungsrechtlich garantiertes Grundrecht auf Bargeld geben muss.
Keywords: D02; E41; E42; 330; cash; public good; basic right